The Role of Self-Esteem in Bullying-Related Depression Among Heterosexual Thai Adolescents: A Cross-Sectional Study. - Pensuksan, Wipawan Chaoum; Saithanwanitkul, Montha; Aekwarangkoon, Saifon (Pacific Rim International Journal of Nursing Research)
Adolescence marks a key stage for emotional regulation and heightened sensitivity to peer influence, during which heterosexual adolescents may be especially vulnerable to depressive symptoms. Approximately one in five Thai adolescents reports bullying, warranting further investigation. Framed within the Cognitive Diathesis-Stress perspective, this study examined depressive symptom prevalence and tested whether self-esteem mediates the link between bullying and depression. This secondary data analysis employed a cross-sectional dataset originally collected in our prior study on depression among Thai adolescents. The present analysis focused on 158 adolescents aged 12-18 years who self-identified as heterosexual. Participants were selected through a multi-stage random sampling process from four secondary schools administered by the Secondary Educational Service Area Office 11 in southern Thailand. Validated tools consisted of the Patient Health Questionnaire for Adolescents, Rosenberg's scale for assessing self-esteem, and the Revised Olweus Bully/Victim Questionnaire. Descriptive statistics, correlation analysis, and mediation testing (PROCESS Macro Model 4) were conducted for data analysis. Approximately 24.1% of participants reported experiencing moderate to severe depressive symptoms. Bullying victimization was correlated positively with depression, whereas self-esteem was negatively associated with both bullying and depression. An indirect pathway via self-esteem was observed, partially explaining the bullying-depression association. These findings support the theoretical pathway in which bullying contributes to depression both directly and indirectly by undermining self-esteem. In nursing practice, early screening and culturally sensitive interventions targeting self-esteem may help buffer the psychological impact of bullying. Future research should explore longitudinal designs and integrated intervention models that further clarify how self-esteem contributes to reducing depressive symptoms in heterosexual adolescent populations.